Gut microbiota and obesity: Impact of antibiotics and prebiotics and potential for musculoskeletal health - Teja Klancic; Raylene A. Reimer (Elsevier, 2020)
Obesity is a complex disease with multiple contributing factors. One of the most intensely studied factors during the past decade has been the gut microbiota, which is the community of all microbes in the intestinal tract. The gut microbiota, via energy extraction, inflammation, and other actions, is now recognized as an important player in the pathogenesis of obesity. Dysbiosis, or an imbalance in the microbial community, can initiate a cascade of metabolic disturbances in the host. Early life is a particularly important period for the development of the gut microbiota, and perturbations such as with antibiotic exposure can have long-lasting consequences for host health. In early life and throughout the life span, diet is one of the most important factors that shape the gut microbiota. Although diets high in fat and sugar have been shown to contribute to dysbiosis and disease, dietary fiber is recognized as an important fermentative fuel for the gut microbiota and results in the production of short-chain fatty acids that can act as signaling molecules in the host. One particular type of fiber, prebiotic fiber, contributes to changes in the gut microbiota, the most notable of which is an increase in the abundance of Bifidobacterium. This review highlights our current understanding of the role of gut microbiota in obesity development and the ways in which manipulating the microbiota through dietary means, specifically prebiotics, could contribute to improved health in the host, including musculoskeletal health. Keywords: Gut microbiota, Musculoskeletal health, Obesity, Prebiotics